2018
DOI: 10.1007/s13167-018-0152-8
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of dental patients determining their compliance level in dentistry: relevance for predictive, preventive, and personalized medicine

Abstract: This article centers on the relationship between psychological specifics of dental patients and their adherence to treatment. It describes clinical and personality specifics of periodontal patients and presents personality characteristics of patients with positive and negative dynamics of the therapy, as well as patients without periodontal diseases. The study findings highlight the importance of building confidential relationships with the patient and the need for a client-oriented approach to developing trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…La utilización de la atención dental en el año estuvo relacionada con la satisfacción con la salud oral (OR = 1,47; p ≤ 0,001). De acuerdo con el tipo de diseño, tres estudios fueron transversales 22,24,26 , uno de casos y controles 21 , uno descriptivo 23 , un análisis crítico 27 , uno de cohorte 25 , uno fenomenológico 20 y un ensayo clínico aleatorizado 28.…”
Section: Resultsunclassified
“…La utilización de la atención dental en el año estuvo relacionada con la satisfacción con la salud oral (OR = 1,47; p ≤ 0,001). De acuerdo con el tipo de diseño, tres estudios fueron transversales 22,24,26 , uno de casos y controles 21 , uno descriptivo 23 , un análisis crítico 27 , uno de cohorte 25 , uno fenomenológico 20 y un ensayo clínico aleatorizado 28.…”
Section: Resultsunclassified
“…For the prevention of oral soft and hard tissues from disease, their surface layers must be intact without bacterial plaque. Several studies showed that verbal recommendations about oral hygiene practices have extremely limited effectiveness [14,15] . Thus, the dentists should focus on patient education and motivation in oral hygiene techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Another important aspect is the “participatory” medicine based on the active participation of population in maintaining oral health. To this end, healthcare will remain insufficient as long as the patient is not motivated and does not feel responsible for their oral health [ 17 , 22 – 24 ]. Contextually, nearly half of chronically diseased people do not comply with adequate medical services suffering from severely progressing pathologies [ 25 ].…”
Section: Introductionmentioning
confidence: 99%